ANALISIS PERHITUNGAN HARGA POKOK PRODUKSI MENGGUNAKAN METODE FULL COSTING STUDI KASUS PADA USAHA D’PETIZ WINS KABUPATEN CIREBON - Dwilaksana, Jidan; Rasmawati, Rasmawati; Tahang, Moh (Sekolah Tinggi Ilmu Ekonomi Ganesha, 2023)
This type of research that uses a qualitative descriptive methodology aims to find out how companies calculate the cost of production using a complete cost calculation approach and how Cirebon Regency, one of the D'Petiz Wins companies, determines thele selling prices. This sample was obtained directly from the D'Petiz Wins office. Cirebon Regency. Data in the form of production coat reports for March and July 2023 are the type of sample used in this study, Literature and documentation reviews were used to obtain data, Culculations with the full costing approuch and the company method are used in technical analysis. The findings of this research indicate that there are differences between the complete costing approach and the company's method of calculating production costs. The selling price generated by the full casting technique will he greater than the selling price generated by the company method because the full costing method uses a higher cost of production calculation than the company method This is thie to variations in the way Industry overhead is hundled. Although a company only accounts for variable costs as production costs, a complete casting technique takes into account all production coats, including fixed and variable costs. Therefore, businesses need to calculate all production costs using a full costing approach to culculate them.